Implementing Parent Engagement Policy in an Increasingly Culturally Diverse Community of New Immigrants: How New is “New”? - Wong, Kathleen King-Yin (Canadian Journal of Education/Revue canadienne de l'éducation, 2015)
The Ontario Ministry of Education announced the Parent Engagement Policy for Ontario Schools in 2010. This policy aims to support parent engagement and provides a vision of its implementation at schools, boards, and the ministry. This mixed methods case study sheds light on its implementation and thus its implication by exploring the parent engagement experiences of parents and teachers. The study results reveal that the actual and desired levels of engagement are different between new immigrants and the established or non-immigrant families, and that teacher education in parent engagement is desirable in optimizing parent partnerships.